The effectiveness of laparoendoscopic single-site surgery (LESS) compared with conventional laparoscopic surgery for ectopic pregnancy with hemoperitoneum - Juseok Yang; Yong Jin Na; Yong Jung Song; Ook Hwan Choi; Sun Kyung Lee; Hwi Gon Kim (Elsevier, 2016)
Objective: The purpose of this study was to compare clinical outcomes of conventional laparoscopic surgery and laparoendoscopic single-site surgery (LESS) in the surgical treatment of tubal ectopic pregnancy. Material and methods: A total of 156 patients were diagnosed with ectopic pregnancies by ultrasonography and serum β-human chorionic gonadotrophin (β-hCG) levels at Pusan National University Yangsan Hospital from January 2009 through December 2013. We excluded 28 patients who only received medical treatment, 15 patients who underwent surgery by laparotomy for severe hypovolemic shock, and 30 patients who presented with less than 1 L of hemoperitoneum. Of the 83 patients with massive hemoperitoneum, 38 patients had LESS performed while the remaining 45 patients underwent conventional laparoscopic surgery. Results: In this study, there were no statistically significant differences in clinical outcomes in either surgical method except for operative time. Operative time of LESS was significantly shorter than conventional surgery for patients with more than 500 mL of hemoperitoneum. Conclusion: LESS is a safe and feasible surgical approach in the treatment of tubal ectopic pregnancy. At the same time, LESS has been shown to be more effective than conventional laparoscopic surgery in handling massive hemoperitoneum of more than 1 L, which is a common complication of ectopic pregnancy.